2021
DOI: 10.1111/febs.15829
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms regulating Proteinase‐Activated Receptors (PARs)

Abstract: Proteinase activated receptors (PARs) are a four-member family of G protein-coupled receptors defined by their irreversible proteolytic mechanism of activation. PARs have emerged as important regulators of various physiological responses and are implicated in numerous pathological conditions. Importantly, PAR1 and PAR4 are critical regulators of platelet function, while PAR2 is well established as a driver of inflammatory responses. PAR targeted drug development efforts are therefore of great interest. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 234 publications
(457 reference statements)
4
44
0
Order By: Relevance
“…However, significantly increased IL-1β mRNA levels were observed in certain brain regions whereas in contrast, TNF-α mRNA levels were reduced. Increased brain cytokine levels are regularly reported in rodent models of sickness and depression-like behaviour (Dantzer 2017;Takahashi et al 2018); therefore, the observed increases in IL-1β mRNA following AC injection are consistent with it playing a role in the PAR2-induced behavioural changes and with elevated cytokine levels reported for other PAR2-related inflammatory disorders (McCulloch et al 2018;Chandrabalan and Ramachandran 2021). Furthermore, we have previously shown that brain IL-1β levels are elevated in LPS-induced sickness behaviour, a condition ameliorated in PAR2 −/− mice, which further supports our conclusion that PAR2 activation results in altered cytokine expression, resulting in AC-induced behavioural changes.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, significantly increased IL-1β mRNA levels were observed in certain brain regions whereas in contrast, TNF-α mRNA levels were reduced. Increased brain cytokine levels are regularly reported in rodent models of sickness and depression-like behaviour (Dantzer 2017;Takahashi et al 2018); therefore, the observed increases in IL-1β mRNA following AC injection are consistent with it playing a role in the PAR2-induced behavioural changes and with elevated cytokine levels reported for other PAR2-related inflammatory disorders (McCulloch et al 2018;Chandrabalan and Ramachandran 2021). Furthermore, we have previously shown that brain IL-1β levels are elevated in LPS-induced sickness behaviour, a condition ameliorated in PAR2 −/− mice, which further supports our conclusion that PAR2 activation results in altered cytokine expression, resulting in AC-induced behavioural changes.…”
Section: Discussionsupporting
confidence: 75%
“…It is now well established that inflammatory mediators are elevated in both patients with depression and rodent models of depression-like behaviour (Miller and Raison 2016 ; Dantzer 2017 ; Felger 2019 ; Branchi et al 2020 ). Similarly, PAR2 has been linked to inflammatory diseases including rheumatoid arthritis and inflammatory bowel disease (Hollenberg et al 2014 ; McCulloch et al 2018 ; Chandrabalan and Ramachandran 2021 ). In agreement with the link between PAR2 and inflammation, we found that AC (100 mg kg −1 ) led to elevated IL-6 levels in blood serum 2-h postinjection whilst IL-1β mRNA was increased and TNF-α mRNA levels reduced in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…PARS can effectively mediate the extracellar signal-regulated kinase (ERK1/2) signal transduction pathway to induce the nuclear reaction and activate a variety of cellular transcription factors (Yoon et al, 2017). Its physiological functions include inducing coagulation response, promoting cell division and proliferation, releasing inflammatory mediators or cytokines to regulate the local inflammatory response, and regulating vascular tension (Chandrabalan and Ramachandran, 2021;Lucena and McDougall, 2021). Activation of PARs can also stimulate cytoplasmic the phospholipase C, phospholipase A, phospholipase D, protein kinase C, mitogenactivated protein kinase (MAPK) and tyrosine protein kinase, temporarily increased cytoplasmic free calcium concentration, opened cell membrane ion channels, and promoted cellular growth (Aldrovandi et al, 2017;Thibeault et al, 2020).…”
Section: Protease Activated Receptor 1/4mentioning
confidence: 99%
“…As observed for other GPCRs, PAR1 internalization by endocytosis requires both clathrin and dynamin [ 70 , 71 ]. Even when the stimulus is absent, PAR1 continues to circulate between the cell membrane and the intracellular compartment, thereby maintaining a stable pool of the receptor on the surface [ 72 , 73 ].…”
Section: Protease-activated Receptor 1 (Par1) General Features and Activation Mechanismmentioning
confidence: 99%
“…In general, biased agonism is the ability of different ligands to act at the same GPCR but triggering distinct cellular signaling (for a recent review, see [ 72 , 73 ]).…”
Section: Protease-activated Receptor 1 (Par1) General Features and Activation Mechanismmentioning
confidence: 99%